Green marketing strategies and customer satisfaction in rural accommodations: A configurational approach - Dias, Á.; Santos, M.; Pereira, L. (Journal of Tourism, Heritage and Services Marketing, 2024)
Rural tourism has become more popular in the tourism industry, as it offers unique and personalized experiences. During the COVID pandemic, many rural accommodations (RA) had more bookings. This shows the importance of finding out the factors that make good RA experiences. Customer ratings are one way to measure customer satisfaction. However, there is not much research on the factors that affect ratings. As such, this study aims to analyze the factors that lead to high and low customer ratings in RAs. Data from 73 rural accommodations was analyzed using fsQCA as a method to study different RAs in Portugal. Our study finds two combinations that lead to high ratings. One combination is for customers who want diversity in experiences, products and services. The other combination is for customers who want premium, expensive and sustainable experiences. For both, diversity in bedroom choice is also important. Our study also finds three combinations that lead to low ratings. These often involve bad bedroom choice and high prices. These results can help managers to be more competitive in the RA market.